Airway responsiveness of firefighters after smoke exposure. Issue 8 (August 1990) - Chia, K S; Jeyaratnam, J; Chan, T B; Lim, T K
Abstract : Ventilatory function and airway reactivity of 20 firefighters were studied one hour before and one hour after exposure in a smoke chamber. None showed an increase in airway reactivity to inhaled histamine before exposure. Eight (80%) of the regular firefighters, however, had an increase in airway reactivity after exposure in the smoke chamber. After six hours, three of the firefighters still had increased airway reactivity. All were non-reactive after 24 hours but the ventilatory function of the three firefighters who were reactive after six hours did not return to baseline values. The duration of service as a firefighter is the major contributing factor to the change in airway reactivity. This increase in airway responsiveness among regular firefighters suggests that some form of chronic epithelial injury is needed before an increase in airway responsiveness is seen.